The Influence of Employee and Investor Pressure, Profitability, and Company Activities on Sustainability Reporting Quality - Made Agus Darma Cahyadi; I Gusti Ayu Made Asri Dwija Putri (E-Jurnal Akuntansi, 2026)
Sustainability reporting is defined as the practice of disclosing and measuring a company's activities as a responsibility to all stakeholders concerning the organization's performance and effectiveness in attaining sustainable development goals. This research aimed to analyze and obtain empirical evidence of the effects of employee pressure, investor pressure, profitability, and company activities on the quality of sustainability reports. The theoretical frameworks utilized were stakeholder theory and legitimacy theory. The population included all energy companies listed on the IDX from 2019-2022. A total of 66 samples were selected using purposive sampling. The analysis was conducted using multiple linear regression. The findings indicate that the quality of sustainability reports is positively affected by employee pressure and profitability. However, it is not influenced by investor pressure or company activities.